1985
DOI: 10.3109/10408448509037459
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and the mechanism of epidermal tumor promotion

Abstract: Chemically induced epidermal carcinogenesis is often divided into two stages: initiation, which involves the conversion of some epidermal cells into latent neoplastic cells, and promotion, which allows the evolution of this neoplastic change into the formation of a neoplasm. The hallmark of epidermal tumor promotion is the transformation of the normal epidermis into a hyperplastic epidermis. A major unanswered question about epidermal tumor promotion is whether the epidermal hyperplasia that characterizes prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…treatment varied by Odc gene dosage. An epidermal hyperplastic response to TPA treatment, which is considered a necessary prerequisite for tumor promotion (15), was observed in Odc +/À mice but was less robust and of shorter duration than the response of wild-type mice. This was true for interfollicular epidermis, but especially so for hair follicles, the presumptive origin of most tumors in the initiation-promotion model (12).…”
Section: Discussionmentioning
confidence: 99%
“…treatment varied by Odc gene dosage. An epidermal hyperplastic response to TPA treatment, which is considered a necessary prerequisite for tumor promotion (15), was observed in Odc +/À mice but was less robust and of shorter duration than the response of wild-type mice. This was true for interfollicular epidermis, but especially so for hair follicles, the presumptive origin of most tumors in the initiation-promotion model (12).…”
Section: Discussionmentioning
confidence: 99%
“…The skin response to TPA is associated with activation of several intracellular pathways (e.g. mitogen-activated protein kinases (MAPKs), AKT, NF-B, STAT3, and AP-1) as well as an increase in the content of chemical mediators, such as cytokines, chemokines, vasoactive peptides, prostaglandins, leukotrienes, and nitric oxide among others (31)(32)(33)(34).In this work, we have investigated skin proliferation and inflammation, before and after TPA application, in mice lacking TR␣1, TR␤, or both genes, comparing these responses with those of hypothyroid animals to distinguish the specific contributions of receptor expression and activation. We found that TRs and thyroid hormones are required for skin homeostasis after TPA treatment and that both receptor genes contribute to…”
mentioning
confidence: 99%
“…The skin response to TPA is associated with activation of several intracellular pathways (e.g. mitogen-activated protein kinases (MAPKs), AKT, NF-B, STAT3, and AP-1) as well as an increase in the content of chemical mediators, such as cytokines, chemokines, vasoactive peptides, prostaglandins, leukotrienes, and nitric oxide among others (31)(32)(33)(34).…”
mentioning
confidence: 99%
“…In addition to the instillation of MNU, we added a wounding procedure. Wounding has long been thought to be a part of carcinogenesis (9) and has proved carcinogenic in mouse skin (9). In addition to the upper airway, our method also produced carcinoma of the esophagus as well as squamous carcinoma of the forestomach of the hamster.…”
Section: Introductionmentioning
confidence: 85%